Issues and Challenges of Cyber Security in India - Sanjay Kumar Gorai,; Sumit Behra,; Maheshwar Kumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This study discusses how cyber security is playing an extremely vital role. It's been one of the hardest jobs during the current modernization,andpreserving privacy and information is a challenging task. The term 'Cyber Protection' has appeared as a nice idea, though its true meaning cannot be explained concisely; previously confused with terms related to anonymities, information sharing knowledge gathering, as well as monitoring. A data security frameworkis urgently required to protect the emerging infrastructure of today's information environment. ICT infrastructure is the common denominator of all critical national infrastructures. The international E-governance and E-commerce projects under implementation include a reliable cyber security infrastructure model. In this article, an effort is made to present a snapshot of this development and possible patterns and imperatives that emerge from this analysis in the sense of India.
Keywords: Cybercrime; Legal Framework; Critical Infrastructure; ICT technology vulnerability; Cyber security structure; electronic security practices; Next Generation Networks; e-governance; e-commerce